Renewable sulfur- and monoterpenes-derived polysulfides as functional crosslinker for epoxy thermosets. (15th January 2020) - Sun, Longfeng; Gao, Shuxi; Gui, Xuefeng; Liu, Lingli; Xu, Kai; Liu, Huan
Graphical abstract: Prepolymer synthesized by sulfur and monoterpenes was used as curing agent and it is an effective utilization of industrial by-products. Highlights: Polymeric Polysulfide–Monoterpene (PST) was synthesized by sulfur and monoterpenes. We use two isomers of monoterpenes to compare the structure and properties of PST. PST is easily dissolve, have high sulfur content and contain terminal thiol group. PST can use as the crosslinking agent for epoxy. The resulting thermoset possess unique properties due to the sulfur-rich polymers (PST). Abstract: Polymer materials, with sulfur as the major part of the backbone structure, are gaining increasing importance because of the large abundance of sulfur and the unique features of polysulfide linkages for modifying material properties. Herein, we introduce polysulfides, which are synthesized from sulfur and monoterpenes, as poly-thiols platform for the crosslinking of epoxy, allowing flexible sulfur constituents incorporate into covalently linked networks. This synthesis can be conducted in a simple, mild, and practical one-pot procedure proceed smoothly in a solvent-free manner with high sulfur utilization to afford sulfur–monoterpene polysulfides (PST) with high sulfur content (up to 58%) and good solubility. The epoxy was cured with PST with imidazole as the catalyst, producing highly sulfur crosslinked thermosets, which is supposed to proceed via a thiol-epoxy reaction mechanism. The resulting thermoset perform good toughness, high transmittance and potential self-healing ability.